ANALISIS BIAYA PRODUKSI GUNA MENENTUKAN HARGA JUAL PT. SELERA RODJO ABADI SEMARANG - Facrul Rozi; Kristianto Shuwiyandi (Worksheet : Jurnal Akuntansi, 2022)
This study aims to determine how to determine the selling price of a product from production costs. The object of this research is PT. Selera Rodjo Abadi which is located on Jl. Bridgen Sudiarto No. 478, Pedurungan Lor, Kec. Pedurungan, Semarang City, Central Java 50246. The research method used in this study is descriptive analysis using the determination of production prices with costing variables and selling prices using the cost plus pricing method. The results of this study indicate that the company in determining the selling price with the cost plus pricing method through the variable costing approach can make it easier to make decisions, especially in determining the selling price of the product.